A Study of the Chinese Rare Books in Lingnan University Library - Yi Chow (Journal of Library and Information Studies, 2012)
The Lingnan University in this article is the Guangzhou Lingnan University, whose forerunner was a Christian College built in 1888 and which ceased operations and was largely absorbed into the Guangzhou Sun Yat-Sen University in 1952. The Chinese rare books of the former Lingnan University Library were by and large merged into the current Sun Yat-Sen University Library and have become a major constituent of its rare books collections. This article analyzes the quantity, sources, and characteristics of the Chinese rare books and shows how the collection development supported the education and research purposes. Lingnan University Library had 174 kinds of Chinese rare books before the Second Sino-Japanese War. It comprised prodominantly Zhao Zeng's collections and the donations of Gantang Xu, Zongzhou Pan, Shaozhen Xu, Hanchen Gan. The Library of Congress of the United States had influenced the collection of local records in Lingnan. The prominent characteristics of the existing collection included the following: (1) it comprises a large quantity of prints and manuscripts of the Ming dynasty; (2) particularly, it highlights the historical and literary records of the Ming; (3) geographically it emphasizes Guangdong records. (Article content in Chinese with English extended abstract)